Nirmatrelvir/ritonavir in COVID-19 patients with haematological malignancies: a report from the EPICOVIDEHA registry. (April 2023) - Salmanton-García, Jon; Marchesi, Francesco; Gomes da Silva, Maria; Farina, Francesca; Dávila-Valls, Julio; Bilgin, Yavuz M.; Glenthøj, Andreas; Falces-Romero, Iker; Van Doesum, Jaap; Labrador, Jorge; Buquicchio, Caterina; El-Ashwah, Shaimaa; et al.
Summary: Background: Nirmatrelvir/ritonavir treatment decreases the hospitalisation rate in immunocompetent patients with COVID-19, but data on efficacy in patients with haematological malignancy are scarce. Here, we describe the outcome of nirmatrelvir/ritonavir treatment in a large cohort of the latter patients. Methods: This is a retrospective cohort study from the multicentre EPICOVIDEHA registry (NCT04733729) on patients with haematological malignancy, who were diagnosed with COVID-19 between January and September 2022. Patients receiving nirmatrelvir/ritonavir were compared to those who did not. A logistic regression was run to determine factors associated with nirmatrelvir/ritonavir administration in our sample. Mortality between treatment groups was assessed with Kaplan–Meier survival plots after matching all the patients with a propensity score. Additionally, a Cox regression was modelled to detect factors associated with mortality in patients receiving nirmatrelvir/ritonavir. Findings: A total of 1859 patients were analysed, 117 (6%) were treated with nirmatrelvir/ritonavir, 1742 (94%) were treated otherwise. Of 117 patients receiving nirmatrelvir/ritonavir, 80% had received ≥1 anti-SARS-CoV-2 vaccine dose before COVID-19 onset, 13% of which received a 2nd vaccine booster. 5% were admitted to ICU. Nirmatrelvir/ritonavir treatment was associated with the presence of extrapulmonary symptoms at COVID-19 onset, for example anosmia, fever, rhinitis, or sinusitis (aOR 2.509, 95%CI 1.448–4.347) and 2nd vaccine booster (aOR 3.624, 95%CI 1.619–8.109). Chronic pulmonary disease (aOR 0.261, 95%CI 0.093–0.732) and obesity (aOR 0.105, 95%CI 0.014–0.776) were not associated with nirmatrelvir/ritonavir use. After propensity score matching, day-30 mortality rate in patients treated with nirmatrelvir/ritonavir was 2%, significantly lower than in patients with SARS-CoV-2 directed treatment other than nirmatrelvir/ritonavir (11%, p = 0.036). No factor was observed explaining the mortality difference in patients after nirmatrelvir/ritonavir administration. Interpretation: Haematological malignancy patients were more likely to receive nirmatrelvir/ritonavir when reporting extrapulmonary symptoms or 2nd vaccine booster at COVID-19 onset, as opposed to chronic pulmonary disease and obesity. The mortality rate in patients treated with nirmatrelvir/ritonavir was lower than in patients with targeted drugs other than nirmatrelvir/ritonavir. Funding: EPICOVIDEHA has received funds from Optics COMMIT (COVID-19 Unmet Medical Needs and Associated Research Extension) COVID-19 RFP program by GILEAD Science, United States (Project 2020-8223 ).